2021
DOI: 10.1021/acs.biochem.1c00003
|View full text |Cite
|
Sign up to set email alerts
|

Smallest Secondary Nucleation Competent Aβ Aggregates Probed by an ATP-Independent Molecular Chaperone Domain

Abstract: Protein oligomerization is a commonly encountered strategy by which the functional repertoire of proteins is increased. This, however, is a double-edged sword strategy because protein oligomerization is notoriously difficult to control. Living organisms have therefore developed a number of chaperones that prevent protein aggregation. The small ATP-independent molecular chaperone domain proSP-C BRICHOS, which is mainly trimeric, specifically inhibits fibril surface-catalyzed nucleation reactions that give rise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(46 citation statements)
references
References 32 publications
1
38
0
Order By: Relevance
“…We then observed kinetic inactivation of protomer-protomer dissociation reactions even for Apentamer dimer. It is noted that A42 pentamer is found in the range of size of experimentally observed soluble A42 oligomers (15,23), and such small oligomeric aggregates are supposed to promote amyloid fibril formation by functioning as secondary nucleation competent aggregates (15). Our observation then suggests that stable formation of this protomer species is involved in a turning point in A42 amyloid fibril formation processes, then giving an important clue toward comprehensive understanding of microscopic mechanisms for shift from the lag phase to the growth phase.…”
Section: Introductionmentioning
confidence: 61%
See 4 more Smart Citations
“…We then observed kinetic inactivation of protomer-protomer dissociation reactions even for Apentamer dimer. It is noted that A42 pentamer is found in the range of size of experimentally observed soluble A42 oligomers (15,23), and such small oligomeric aggregates are supposed to promote amyloid fibril formation by functioning as secondary nucleation competent aggregates (15). Our observation then suggests that stable formation of this protomer species is involved in a turning point in A42 amyloid fibril formation processes, then giving an important clue toward comprehensive understanding of microscopic mechanisms for shift from the lag phase to the growth phase.…”
Section: Introductionmentioning
confidence: 61%
“…The recent experimental studies reported that the number of subunits in soluble A42 aggregates ranges from 4 to 8 (15,23). Besides, such smaller oligomer species are supposed to be secondary nucleation competent fibril-like aggregates which can convert natively folded monomers into growth-competent monomers.…”
Section: Protomer-protomer Dissociation Reaction Is Remarkably Suppressed At the Point Of A42 Pentamer Formationmentioning
confidence: 99%
See 3 more Smart Citations